Association of LEAF-Q and EDE-QS scores with cholesterol levels in Finnish female athletes - Silvennoinen, J. I. K.; Ihalainen, J. K.; Valtonen, M.; Mjøsund, K.; Sipilä, P. N. (International Journal of Sport Nutrition and Exercise Metabolism, 2025)
Low energy availability (LEA) is common in athletes and has been linked to disturbances in sex hormone levels, affecting cholesterol metabolism and potentially increasing cardiovascular risk. Our study examined the relationship between LEA symptoms and eating disorder symptoms with cholesterol levels in a cross-sectional sample of Finnish national- and international-level female athletes. Physiological symptoms of LEA were self-reported using the Low Energy Availability in Females Questionnaire (LEAF-Q, n=176), and eating disorder symptoms with the Eating Disorder Examination Questionnaire Short (EDE-QS, n=294). Athletes representing lean sports (LEAF-Q, n=60; EDE-QS, n=80) were also analysed separately. Serum cholesterol concentrations were measured from venous blood samples. Pearson`s r, linear regression, and logistic regression were used to analyse the relationships between the variables. The prevalence of high LEAF-Q scores (=8 points), suggesting a higher risk of problematic LEA, was 41% across all sports and 47% in lean sport athletes. In the full sample, athletes with LEAF-Q scores above the cut-off (=8) showed a similar risk to clinically elevated LDL cholesterol levels (=3mmol/l) with those who scored below the cut-off (17% vs. 15%, adjusted OR 1.17, 95% CI 0.64-2.15, p=0.62). Athletes with EDE-QS scores above the threshold of =15 were at a higher risk of clinically elevated LDL levels than to those below the threshold (38% vs. 18%, adjusted OR 2.82, 95% CI 1.06-7.05, p=0.030). Also, a one-point increase in LEAF-Q score was linked to a non-significant rise in LDL (beta=0.024, 95% CI -0.0011-0.049, p=0.061), but a one-point increase in EDE-QS score was associated with increased LDL (beta=0.028, 95% CI 0.0098-0.046, p=0.0029). Stronger associations were found in lean sport athletes (LEAF-Q and LDL: beta=0.043, 95% CI 0.0041-0.08, p=0.031; EDE-QS and LDL: beta=0.036, 95% CI 0.0041-0.068, p=0.028). Overall, EDE-QS scores were associated with increased LDL levels in the full sample of female athletes representing mixed sports and both LEAF-Q and EDE-QS scores were associated with increased LDL levels among athletes representing lean sports. Further research should evaluate the long-term impact of LEA and eating disorder symptoms on cardiovascular health in athletes.